ANALISIS KUANTITATIF ISOFLAVON TEMPE SECARA CEPAT DAN SEDERHANA MENGGUNAKAN METODE KROMATOGRAFI LAPIS TIPIS- DENSITOMETRI - Agustina Setiawati; Sri Hartati Yuliani; Enade Perdana Istyastono; Evy Fenny Veronica; Dina Christin Ayuning Putri; Reza Eka Putra; David Chandra Putra; Agnes Mutiara Kurniawan; Michael Raharja Gani (Sanata Dharma University, 2014)
Rapid and simple quantitative analysis isoflavones tempe using densitometric TLChas been done. The mobile phase of the system was chloroform: methanol: ethylacetate (45: 5:0.75). Thin layer chromatography was performed on aluminium TLC plates.Ascending distanceof 1 ?L sample was performanced 10 cm. Then the plate was scanned at 261 nm. A linearrelationship obtained at 0.08 - 2 ?g/spot with r= 0.9986. The LOD and LOQ of isoflavone were0.014 ?g/spot and 0.048 ?g/spot. Genistein contained in tempe was 0.151 0.005 % b/b.